Development of Islamic banking laws in Nigeria - Abdullahi, Nura Sani (Ahmad Ibrahim Kulliyyah of Laws, International Islamic University Malaysia, 2017)
The Islamic banking system has been in existence in Nigeria for almost six years. Banks and Other Financial Institutions Act 1991 (BOFIA) (as amended) permits the establishment of profit and loss sharing which leads to the emergence of Islamic banking in Nigeria as a category of the non-interest banking. The Central Bank of Nigeria Act 2007 (CBNA) and BOFIA empower the Central Bank of Nigeria (CBN) to issue guidelines to any institution under its supervision. In an attempt to develop Islamic banking laws in Nigeria, the CBN has issued various guidelines to govern Islamic financial institutions in the country. This study focuses on the development of Islamic banking laws in Nigeria by examining, evaluating and scrutinizing the laws. Data was obtained through the primary and secondary sources, such as statutes, regulations, guidelines, textbooks and articles. The study finds that there are significant developments in Islamic banking laws in Nigeria, starting from the 1991 amendment of BOFIA. Moreover, between 2009 and 2015 the CBN released different regulations and guidelines in relation to the scope, conditions and minimum standards of capital ratio, regulation and supervision, Shariah governance and advisory committees for all Non-Interest Financial Institutions in Nigeria. It is hoped that the Islamic banking laws in Nigeria will be developed further with the issuance of more guidelines by the regulatory body when it deems necessary. It is suggested that the National Assembly should review the provisions of the Federal Constitution of the Republic of Nigeria to empower the Shariah Court of Appeal to hear and decide any dispute on Islamic banking matters. Otherwise, a special court with specific jurisdiction to hear and decide Islamic banking and finance matters should be established within the Federal High Court. Reference to the Financial Regulation Advisory Council of Experts (FRACE) by the Federal High Court and arbitrator should also be made when dealing with Shariah issues in any dispute on Islamic banking and finance. In addition, the regulatory body should also provide comprehensive regulations on Islamic liquidity management instruments and review the guidelines on tax incentives on Islamic banking products.